Хімічне осадження карбонату кальцію різних кристалічних модифікацій - Михайлова, Євгенія Олександрівна; Мороз, Микола Олександрович; Сінческул, Олександр Леонідович (НТУ "ХПІ", 2017)
Досліджено процес осадження карбонату кальцію з рідинних відходів содових виробництв. Встановлено, що за різних технологічних умов утворюється осад СаСО₃ з різним вмістом кальциту, ватериту та арагоніту. Визначено параметри процесу, що дозволяють одержати продукт з максимально можливим вмістом кальциту, який є найбільш стійною кристалічною модифікацією. Це впливатиме на властивості хімічно осадженого карбонату кальцію як наповнювача.

The general characteristic of calcium carbonate, which is widely used as filler in the creation of various composite materials, is given. The state of manufacture of the product in Ukraine is analyzed. The advantages of chemically precipitated CaCO3 in comparison with the natural crushed material are shown. It is suggested to use liquid waste of soda production as a raw material for obtaining a synthetic product. The methods of experimental studies of the calcium carbonate deposition process and laboratory analysis of the resulting precipitate and mother liquor are described. It was determined that according to different technological conditions a precipitate of CaCO₃ with different content of calcite, vaerite and aragonite is formed. The parameters of the process, that allows getting the product with the maximum possible content of calcite, which is the most stable crystalline modification, are determined. This will affect the properties of chemically precipitated calcium carbonate as filler and will allow it to be used directly in the manufacture of paper, rubber and plastics.
Chemical precipitation of various crystalline modifications of calcium carbonate
Keywords: кальцит; арагоніт; ватерит; calcite; aragonite; vaterite